Sexual dimorphism in the physiological function of ATP-sensitive potassium channels - Colburn, Trenton David (Kansas State University, 2020)
ATP-sensitive K⁺ (K[subscript ATP]) channels are metabolic sensors present in vascular (endothelial), muscle (smooth, cardiac and skeletal), nervous and pancreatic tissues which open in response to a decreasing ATP:ADP ratio (i.e., during exercise and/or hypoxia) and close following pharmacological blockade (i.e., sulphonylureas such as glibenclamide (GLI)). Comprised of four pore-forming inward rectifying K⁺ subunits surrounded by four sulphonylurea receptors, vascular K[subscript ATP] channels support increased muscle blood flow (Q̇m) and microvascular oxygen delivery (Q̇O[subscript 2mv])-to-utilization (V̇O[subscript 2mv]) matching (PO[subscript 2mv]) in exercising/contracting skeletal muscle by hyperpolarizing smooth muscle cells via K⁺ efflux and subsequently reducing the influx of calcium ions. There is also evidence that K[subscript ATP] channels limit myocardial damage following ischemia in a sex-dependent manner, via greater ventricular K[subscript ATP] channel content in females. GLI is a commonly prescribed diabetes medication that inhibits pancreatic K[subscript ATP] channels and increases insulin release. Unfortunately, one off-target consequence of GLI is inhibition of vascular K[subscript ATP] channel-mediated vasodilation which may impair exercise tolerance. Therefore, the overall aim of this dissertation was to determine whether vascular K[subscript ATP] channel function supports exercise tolerance, and whether sex differences in K[subscript ATP] channel function exist in determining fast-twitch oxidative muscle Q̇O₂ and V̇O₂; since this muscle type is recruited at the threshold between heavy- and severe-intensity exercise in humans leading to V̇O[subscript 2max] and exhaustion. In order to assess Q̇O₂ and V̇O₂ in subsequent K[subscript ATP] channel studies, our first investigation (Chapter 2) compared the partial pressure of O₂ in the interstitial (PO[subscript 2is]) and microvascular (PO[subscript 2mv]) compartments during twitch contractions in muscles spanning the range of fiber types and oxidative capacity. We demonstrated that a significant resistance to transcapillary O₂ flux resides in all muscles such that PO[subscript 2is] is significantly lower than PO[subscript 2mv] (transcapillary PO₂ = PO[subscript 2mv] – PO[subscript 2is]), and that this resistance was lowest in highly oxidative fast-twitch muscle. This novel finding provided the ability to estimate PO[subscript 2mv] from PO[subscript 2is] measurements in Chapters 3 and 4, and estimate convective (Q̇O₂) and diffusive (DO₂) O₂ transport since the convergence of Q̇O₂ and DO₂ establishes muscle O₂ utilization (V̇O₂). In the second investigation (Chapter 3), we demonstrated that systemic GLI administration in female rats reduced V̇O[subscript 2max] and submaximal exercise tolerance during treadmill running (critical speed (CS), metabolic threshold separating heavy-intensity exercise from severe-intensity exercise which leads to V̇O[subscript 2max]). Topical administration of GLI via superfusion onto fast-twitch oxidative muscle impaired Q̇m and PO[subscript 2is] and subsequently lowered V̇O₂ during twitch contractions via reduced Q̇O₂ and DO₂. The third investigation further utilized male and ovariectomized female (F+OVX) rats (Chapter 4) to assess sex differences in vascular K[subscript ATP] channel function (male vs female) and the effect of ovariectomy (female vs F+OVX; models for pre- and post-menopause). GLI superfusion lowered V̇O₂ via impaired Q̇m and Q̇O₂, and thus PO[subscript 2is], in male and female, but not F+OVX, rats. Furthermore, females demonstrated impaired DO₂ which, in combination with impaired Q̇O₂, would help describe or account for the greater GLI-induced speeding of PO[subscript 2is] fall during the rest-contraction transient compared to males. Collectively, the results herein demonstrate that vascular K[subscript ATP] channels support submaximal exercise tolerance in health via improved convective and diffusive O₂ transport in fast-twitch oxidative muscle. GLI-induced K[subscript ATP] channel inhibition lowers the threshold separating heavy- and severe-intensity exercise (i.e., CS) and ultimately leads to compromised V̇O[subscript 2max] and earlier onset of exhaustion. Furthermore, exercise intolerance and adverse cardiovascular events in diabetic patients may be further exacerbated by sulphonylurea medication, especially in premenopausal females.
Keywords: Vascular control; Microcirculation; Skeletal muscle oxygenation; Sex; Sulphonylurea; Exercise tolerance